Про квадратный трехчлен f(x)=x^2+px+q известно, что f(1)f(-1)=f()2f(-2), а f(3)=2. найдите f(-3)

teaego teaego    3   13.09.2019 01:50    0

Ответы
РОЗОЧКА37563 РОЗОЧКА37563  07.10.2020 10:53
Решение смотри на фото
ПОКАЗАТЬ ОТВЕТЫ
LizokJUISE LizokJUISE  07.10.2020 10:53
F(1) = 1 + p + q
f(-1) = 1 - p + q
f(2) = 4 + 2p + q
f(-2) = 4 - 2p + q
f(3) = 9 + 3p + q = 2; q = -3p - 7
f(1)*f(-1) = f(2)*f(-2)
(1 + p + q)(1 - p + q) = (4 + 2p + q)(4 - 2p + q)
Раскрываем скобки
1+p+q-p-p^2-pq+q+pq+q^2 = 16+8p+4q-8p-4p^2-2pq+4q+2pq+q^2
Упрощаем
1 + q - p^2 + q = 16 + 4q - 4p^2 + 4q
3p^2 - 15 - 6q = 0
p^2 - 2q - 5 = 0
p^2 - 2(-3p - 7) - 5 = 0
p^2 + 6p + 9 = 0
(p + 3)^2 = 0
p = -3
q = -3p - 7 = 9 - 7 = 2
Трехчлен: f(x) = x^2 - 3x + 2
f(-3) = 9 - 3*(-3) + 2 = 20

Про квадратный трехчлен f(x)=x^2+px+q известно, что f(1)f(-1)=f()2f(-2), а f(3)=2. найдите f(-3)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика